2020
DOI: 10.1101/2020.11.13.381798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathway-extended gene expression signatures integrate novel biomarkers that improve predictions of patient responses to kinase inhibitors

Abstract: Cancer chemotherapy responses have been related to multiple pharmacogenetic biomarkers, often for the same drug. This study utilizes machine learning to derive multi-gene expression signatures that predict individual patient responses to specific tyrosine kinase inhibitors, including erlotinib, gefitinib, sorafenib, sunitinib, lapatinib and imatinib. Support Vector Machine learning was used to train mathematical models that distinguished sensitivity from resistance to these drugs using a novel systems biology-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 96 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Both FSFS and BSFS models were derived from the top 50 ranked mRMR genes, in addition to other published radiation responsive genes: AEN , BAX , BCL2 , DDB2 , FDXR , PCNA , POU2AF1 , and WNT3 . SVMs were derived with a Gaussian radial basis function kernel by iterating over box-constraint (C) and kernel-scale (σ) parameters and gene features, minimizing to either misclassification or log loss by cross- validation (Zhao et al 2018a; Bagchee-Clark et al 2020). Gene signatures were then assessed with a validation dataset and re-evaluated (by misclassification rates, log loss, Matthews correlation coefficient, or goodness of fit).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both FSFS and BSFS models were derived from the top 50 ranked mRMR genes, in addition to other published radiation responsive genes: AEN , BAX , BCL2 , DDB2 , FDXR , PCNA , POU2AF1 , and WNT3 . SVMs were derived with a Gaussian radial basis function kernel by iterating over box-constraint (C) and kernel-scale (σ) parameters and gene features, minimizing to either misclassification or log loss by cross- validation (Zhao et al 2018a; Bagchee-Clark et al 2020). Gene signatures were then assessed with a validation dataset and re-evaluated (by misclassification rates, log loss, Matthews correlation coefficient, or goodness of fit).…”
Section: Methodsmentioning
confidence: 99%
“…Several groups (Boldt et al 2012;Budworth et al 2012;Knops et al 2012;Ghandhi et al 2017) have also used signatures to determine radiation exposures. Biochemically-inspired machine learning is a robust approach to derive diagnostic gene signatures for chemotherapy (Dorman et al 2016;Mucaki et al 2016;Mucaki et al 2019;Bagchee-Clark et al 2020) as well as radiation (Zhao et al 2018a). Given the limited sample sizes of typical datasets, appropriate ML methods for deriving gene signatures have included Support Vector Machines, Random Forest classifiers, Decision Trees, Simulated Annealing, and Artificial Neural Networks (Rogan, 2019;Boldrini et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both genomic complexity- and physiology-based approaches are necessary to understand the relationship between genotypes and phenotypes. Finally, Bagchee-Clark et al ( 2020 ) have shown that machine learning-based, pathway-extended gene expressions measurements can be successfully used to identify novel biomarkers that improve predictions of patient response to drugs in cancer therapy.…”
Section: Pathway-based Approaches Would Provide a Handle On Network Complexitymentioning
confidence: 99%